Faith in a seed : - Thoreau, Henry David (Island Press/Shearwater Books, 1993)
This book represents nothing less than a triumph of editorial skill and integrity over conventional wisdom. A study of plant ecology using Darwinian theory, Faith in a Seed is one of the more interesting books published in our time, so felicitously does it give readers a fresh dose of all that makes Thoreau such a major figure in American letters. The holograph of The Dispersion of Seeds , Thoreau's last major project (as well as the manuscript of Wild Fruits, selections of which appear here along with two other writings probably intended for the title volume) was dismissed by most of the scholars who even knew of it as being taxonomically suspect, uninterestingly concrete, and "best left unpublished." How wrong. It is, in fact, the book that latter-day Thoreau admirers have often wished he had written: sensual, acute, intricate, and altogether fascinating, a text that should cause scholars to reevaluate their assessment of an important writer.